Sja-miR-71a in Schistosome egg-derived extracellular vesicles suppresses liver fibrosis caused by schistosomiasis via targeting semaphorin 4D. Issue 1 (1st January 2020) - Wang, Lifu; Liao, Yao; Yang, Ruibing; Yu, Zilong; Zhang, Lichao; Zhu, Zifeng; Wu, Xiaoying; Shen, Jia; Liu, Jiahua; Xu, Lian; Wu, Zhongdao; Sun, Xi
ABSTRACT: Schistosomiasis is characterized by liver fibrosis, and studies have indicated that Schistosoma japonicum ( S. japonicum ) eggs can limit the progression of liver fibrosis. However, the detailed molecular mechanisms are yet unclear. Extracellular vesicles (EVs) contain a selection of miRNAs for long-distance exchange of information and act as an important pathway for host-parasite communication. This study aimed to explore the potential role of S. japonicum egg-derived EVs and its key miRNA in liver fibrosis. Herein, we found that S. japonicum egg-derived EVs can inhibit the activation of hepatic stellate cells, which is mediated via the high expression of Sja-miR-71a. Sja-miR-71a in EVs attenuates the pathological progression and liver fibrosis in S. japonicum infection. Sja-miR-71a inhibiting TGF-β1/SMAD and interleukin (IL)-13/STAT6 pathways via directly targeting semaphorin 4D (Sema4D). In addition, Sja-miR-71a can also suppress liver fibrosis by regulating Th1/Th2/Th17 and Treg balance. This study contributes to further understanding of the molecular mechanisms underlying Schistosoma -host interactions, and Sema4D may be a potential target for schistosomiasis liver fibrosis treatment.